Evaluation of Local Government Policy Towards Improving Coastal Waste Management - Cintanesa, Esti; Stefani, Stefani; Manurung, Suryana (Jurnal Studi Ilmu Pemerintahan, 2023)
This research focuses on the complex issue of coastal waste management, especially in Tanjungpinang City, Indonesia, which has excellent potential to generate coastal waste. This research aims to evaluate the extent to which government policies in managing coastal waste in Pelantar II of Tanjungpinang City have been implemented. The research method used is qualitative, with data collection through literature studies. The results showed that implementing government policies in managing coastal waste in Pelantar II Tanjungpinang City still faced several obstacles. One of the main obstacles is the need for more community participation in managing coastal waste. This is caused by several factors, including the lack of facilities, especially landfills, in the neighborhood. In addition, the implementation of existing regulations could be more robust. These findings underscore the importance of the government and community's roles in addressing the coastal waste problem. The government must improve infrastructure and facilities that support more effective waste management, including developing suitable landfills. It is also essential to strengthen the implementation of existing regulations and raise public awareness of the importance of maintaining coastal cleanliness. The results of this study provide a deeper understanding of the challenges faced in managing coastal waste in Pelantar II Tanjungpinang City and highlight the need for joint efforts between the government and the community to achieve better coastal waste management.